Matemática no Brasil: as traduções de Manoel Ferreira de Araújo Guimarães (1777-1838) das obras de Adrien Marie Legendre - Trentin, Paulo Henrique (2011)
This thesis addresses the life and works of Manoel Ferreira de Araújo Guimarães (1777-1838), a major author in the History of Brazilian Mathematics. The study centers on the translation by Manoel Ferreira de Araújo Guimarães of Éleménts de Geométrie e Traité de Trigonométrie, written by Adrien Marie Legendre (1752-1833), as important contributions to the process of institutionalizing the teaching of Mathematics in Brazil at the beginning of the 19th century. The analysis of Guimarães´s translations helped shed light on the reasons that led the translator to propose changes and, based on the identification of some of his interlocutors, understand what directed Guimarães to the works of Adrien Marie Legendre. Regarding further works by the Brazilian mathematician, we have been able to identify, directly or indirectly, scholars who had access to his translated works. Therefore, this study is intended to contribute to researchers who seek to (re)study the period ranging from the beginning to the first half of the 19th century, on the teaching of Mathematics in Brazil